2018
DOI: 10.1002/dmrr.3043
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome in type 1 diabetes: A comprehensive review

Abstract: SummaryType 1 diabetes (T1D) is an autoimmune disease, which is characterized by the destruction of islet β cells in the pancreas triggered by genetic and environmental factors. In past decades, extensive familial and genome‐wide association studies have revealed more than 50 risk loci in the genome. However, genetic susceptibility cannot explain the increased incidence of T1D worldwide, which is very likely attributed by the growing impact of environmental factors, especially gut microbiome. Recently, the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
141
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(146 citation statements)
references
References 105 publications
(176 reference statements)
1
141
0
4
Order By: Relevance
“…Moreover, different artemether derivatives were used in various mouse models or cells, which may lead to different conclusions. Second, Chinese traditional medicine, such as berberine, has been shown to be potent in modulating gut microbiota (45,46). Artemether and its derivatives might have differential roles in the changes of gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, different artemether derivatives were used in various mouse models or cells, which may lead to different conclusions. Second, Chinese traditional medicine, such as berberine, has been shown to be potent in modulating gut microbiota (45,46). Artemether and its derivatives might have differential roles in the changes of gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…6 Linkage analysis and genome-wide association studies have identified more than 50 type 1 diabetes mellitus susceptibility genes. 7 Environmental factors also play a role in type 1 diabetes mellitus susceptibility. Viruses or environmental toxins may enhance the progression of type 1 diabetes mellitus by inducing insulitis, an inflammatory infiltrate in the islets of Langerhans found in the pancreas, or by activating the immune system through molecular mimicry of islet autoantigens.…”
Section: E Ti Ology and Epidemi Ology Of Diabe Te Smentioning
confidence: 99%
“…Viruses or environmental toxins may enhance the progression of type 1 diabetes mellitus by inducing insulitis, an inflammatory infiltrate in the islets of Langerhans found in the pancreas, or by activating the immune system through molecular mimicry of islet autoantigens. 7 Use of antibiotics has also been implicated in the pathogenesis of type 1 diabetes mellitus but their role is still controversial. The etiology of type 2 diabetes mellitus is intricate and related to risk factors such as age, genetics, race, and ethnicity, as well as environmental factors such as diet, physical activity, and smoking.…”
Section: E Ti Ology and Epidemi Ology Of Diabe Te Smentioning
confidence: 99%
“…Furthermore, intraperitoneal injection of 1,25(OH) 2 D 3 (5 ng/g body weight) for 1 month attenuated metabolic endotoxemia (as evidenced by lower plasma lipopolysaccharides (LPS)) and improved intestinal tight junction integrity, as well as Paneth cell defence in HFD + VDD‐fed mice . An elegant review by Zheng and colleagues showed that evidence is accumulating for a role of vitamin D in improved beta cell function in type 1 diabetes (T1D), possibly via effects on the microbiome . Nevertheless, the underlying mechanisms still need further investigations.…”
Section: Role Of Vitamin D In Gutmentioning
confidence: 99%